2018
DOI: 10.1017/s1478951518000214
|View full text |Cite
|
Sign up to set email alerts
|

Addressing cancer patient and caregiver role transitions during home hospice nursing care

Abstract: A secondary, qualitative analysis was conducted on transcripts. Using an iterative process of constant comparison, coders inductively categorized nurse, caregiver, and patient communication behavior into overarching themes. Participants were home hospice nurses and cancer patient/spouse caregiver dyads; participants were >45 years of age, English speaking, and cognitively able to participate. Research took place in the home during nurse visits.ResultNineteen unique home hospice visits were analyzed. Patient-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The study findings are similar to previous studies showing that family caregivers have difficulties providing post-discharge in-home care for patients with an incurable disease, unstable illness condition, or disability in daily living [22,23,27,43,57]. These difficulties increase family caregivers' perceived care burden and difficulties in providing their patients with post-discharge in-home care [19,28,[58][59][60]. Among the most challenging care burdens experienced by family caregivers were emergency events and care needs, which affected their readiness for their patient's discharge home [22,23,27,31,32,61].…”
Section: Family Caregivers' Concerns Regarding In-home Caresupporting
confidence: 87%
See 2 more Smart Citations
“…The study findings are similar to previous studies showing that family caregivers have difficulties providing post-discharge in-home care for patients with an incurable disease, unstable illness condition, or disability in daily living [22,23,27,43,57]. These difficulties increase family caregivers' perceived care burden and difficulties in providing their patients with post-discharge in-home care [19,28,[58][59][60]. Among the most challenging care burdens experienced by family caregivers were emergency events and care needs, which affected their readiness for their patient's discharge home [22,23,27,31,32,61].…”
Section: Family Caregivers' Concerns Regarding In-home Caresupporting
confidence: 87%
“…Previous studies have highlighted that family caregivers can perceive a lack of adequate knowledge of and information on patient care and symptom management during the discharge process while preparing to care for advanced cancer patients with severe illness with poor performance status and an increased dependence on life care, which ultimately affects their readiness for the patient's hospital discharge [12,16,17]. Furthermore, many family caregivers of advanced cancer patients experience post-discharge care burdens [18,19] and worry about being unable to provide symptom distress and emergency health event management at home [12,[20][21][22][23][24][25]. Compared with hospitalisation, home care involves fewer human resources and professional skills and less equipment support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The caregivers in the study reported that they felt isolated and did not have enough time to go out or receive visits. Because of the constant demands of care that need to be met with the utmost attention, caregivers' personal relationships are often affected 28 …”
Section: Discussionmentioning
confidence: 99%
“…The goal of nursing is “patient satisfaction, social satisfaction, government satisfaction.” The whole nursing process requires nursing staff to provide continuous, satisfactory, and whole-process nursing services. Changing the situation where patients or their families hire nursing workers to make up for the lack of nursing work and improve the nurse-patient relationship [ 19 , 20 ]. The control group's time to get out of bed, postoperative eating time, postoperative exhaust time, and hospital stay were longer than those of the study group.…”
Section: Discussionmentioning
confidence: 99%